Human islets contain a subpopulation of glucagon-like peptide-1 secreting α cells that is increased in type 2 diabetes - Scott A. Campbell; Dominic P. Golec; Matt Hubert; Janyne Johnson; Nicole Salamon; Amy Barr; Patrick E. MacDonald; Koenraad Philippaert; Peter E. Light (Elsevier, 2020)
Objectives: Our study shows that glucagon-like peptide-1 (GLP-1) is secreted within human islets and may play an unexpectedly important paracrine role in islet physiology and pathophysiology. It is known that α cells within rodent and human pancreatic islets are capable of secreting GLP-1, but little is known about the functional role that islet-derived GLP-1 plays in human islets. Methods: We used flow cytometry, immunohistochemistry, perifusions, and calcium imaging techniques to analyse GLP-1 expression and function in islets isolated from cadaveric human donors with or without type 2 diabetes. We also used immunohistochemistry to analyse GLP-1 expression within islets from pancreatic biopsies obtained from living donors. Results: We have demonstrated that human islets secrete ∼50-fold more GLP-1 than murine islets and that ∼40% of the total human α cells contain GLP-1. Our results also confirm that dipeptidyl peptidase-4 (DPP4) is expressed in α cells. Sitagliptin increased GLP-1 secretion from cultured human islets but did not enhance glucose-stimulated insulin secretion (GSIS) in islets from non-diabetic (ND) or type 2 diabetic (T2D) donors, suggesting that β cell GLP-1 receptors (GLP-1R) may already be maximally activated. Therefore, we tested the effects of exendin-9, a GLP-1R antagonist. Exendin-9 was shown to reduce GSIS by 39% and 61% in ND islets and T2D islets, respectively. We also observed significantly more GLP-1+ α cells in T2D islets compared with ND islets obtained from cadaveric donors. Furthermore, GLP-1+ α cells were also identified in pancreatic islet sections obtained from living donors undergoing surgery. Conclusions: In summary, we demonstrated that human islets secrete robust amounts of GLP-1 from an α cell subpopulation and that GLP-1R signalling may support GSIS to a greater extent in T2D islets.